2005
DOI: 10.1016/j.virol.2004.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of primary HPV16- and HPV18-infected early stage cervical cancers and normal cervical epithelium: identification of novel candidate molecular markers for cervical cancer diagnosis and therapy

Abstract: With the goal of identifying genes with a differential pattern of expression between invasive cervical carcinomas (CVX) and normal cervical keratinocytes (NCK), we used oligonucleotide microarrays to interrogate the expression of 14,500 known genes in 11 primary HPV16 and HPV18-infected stage IB-IIA cervical cancers and four primary normal cervical keratinocyte cultures. Hierarchical cluster analysis of gene expression data identified 240 and 265 genes that exhibited greater than twofold up-regulation and down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
123
1
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(143 citation statements)
references
References 38 publications
13
123
1
6
Order By: Relevance
“…18,19 In our study, the analysis of these biomarkers in biopsy material by immunohistochemistry showed that all were positive in a high proportion of the HSIL lesions, which is consistent with current evidence. 8,16,[20][21][22][23] Nevertheless, immunohistochemistry is not adequate for screening purposes. Finally, immunohistochemistry only analyzes a small area of the lesion, which may not be representative of the whole process that could explain the absence of correlation between the mRNA expression in the liquid-based cytology and the immunohistochemistry staining in the simultaneous biopsy for most of the biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 In our study, the analysis of these biomarkers in biopsy material by immunohistochemistry showed that all were positive in a high proportion of the HSIL lesions, which is consistent with current evidence. 8,16,[20][21][22][23] Nevertheless, immunohistochemistry is not adequate for screening purposes. Finally, immunohistochemistry only analyzes a small area of the lesion, which may not be representative of the whole process that could explain the absence of correlation between the mRNA expression in the liquid-based cytology and the immunohistochemistry staining in the simultaneous biopsy for most of the biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The list of candidates who have shown potential utility in cervical cancer screening includes p16 INK4a (CDKN2A), survivin (BIRC5), metalloproteinase 9 (MMP9), topoisomerase 2 alpha (TOP2A), minichromosome maintenance 5 (MCM5), or MKi67 proteins (MKI67). [7][8][9] Most studies focused on these biomarkers have used immunohistochemistry to detect protein expression. However, several shortcomings of immunohistochemistry, in particular the interobserver variation inherent to all morphological techniques and the difficulty to obtain reproducible quantification, hamper proper evaluation of the clinical usefulness of these biomarkers.…”
mentioning
confidence: 99%
“…However, the effect of high-risk HPV on global gene expression has been studied and characterised in several model systems on different microarray platforms (Chang and Laimins, 2000;Nees et al, 2001;Alazawi et al, 2002;Vernell et al, 2003;Garner-Hamrick et al, 2004;Loercher et al, 2004;Santin et al, 2005). Several biomarkers predicting both HPV status and response to treatment for several cancers have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting hierarchical clustering (Figure 3Ad) was highly similar to both the hierarchical clustering of our unsupervised analysis (Figure 3Aa) and to the hierarchical clustering of genes selected by performing two independent statistical analyses between the two tumour groups (Figure 3Ab and Ac). Similarly, to investigate the possible transcriptional influence of high-risk HPV, we performed hierarchical cluster analysis on genes reported differentially Figure 3 (A) Hierarchical clustering of the unsupervised analysis on (Aa) the selection of 8449 probes, (Ab) the 337 individual genes defined by the Ttest, (Ac) the 363 individual genes defined by the SAM analysis together with collections of genes described by others relevant to our study and included within the group of 8449 probes, (Ad) HPV16-induced gene expression (Alazawi et al, 2002), (Ae) HPV16 E6/E7-induced gene expression (Nees et al, 2001), (Af) HPV31-induced gene expression (Chang and Laimins, 2000), (Ag) Gene expression in SSC (Loercher et al, 2004), (Ah) E2F-regulated genes (Ishida et al, 2001), (Ai) HPV16-and HPV18-induced gene expression (Santin et al, 2005) and, finally, (Aj) HPV18 E6/E7-induced gene expression (GarnerHamrick et al, 2004). (B) The total number of genes within each report cited.…”
Section: Microarray Analysismentioning
confidence: 99%
See 1 more Smart Citation